Albania : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
In the aftermath of adverse supply shocks, and with further measures to promote investment, growth of production and exports is expected to recover. Efforts to remove barriers to investment and ensure a reliable provision of electricity are critical to private-sector-led growth. External sustainability hinges on further improvements in the business climate to expand the production of tradables, and ongoing fiscal consolidation. Although the Albanian government remains committed to the program, serious risks to growth and the execution of the poverty reduction strategy remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet